DO YOU CAPTURE FINANCIAL CRISIS? - Mukhlisin, Murniati; Komalasari, Ratna (Journal of Islamic Monetary Economics and Finance, 2018)
This article summarizes the multitude of empirical studies in the area of Islamic banking and finance with purpose to analyze impact of Islamic banking and finance studies to practice by mapping research direction and the depth of the study. The studies are categorized based on research paradigm, countries being researched, methods employed, and results that lead to policy direction in the particular period. The research found that the research direction of the papers under study mostly employ positivist paradigm with countries being researched are generally Malaysia, Pakistan, Indonesia and UAE. It documents that the papers did not link directly to the future policy directions ie. to predict and prepare for financial crisis, rather they merely responded to the undergoing policies or themes of the journals. This review provides insights for understanding the importance of guiding future policy direction in the area of Islamic banking and finance by publishing more research policy papers authored by both academics and professionals.